Espiritualidade, saúde integral e complexidade: faces e interface. - Fonseca, Marcos Lucena da (2024)
We start from the idea that the human being is not dual - mind and body - but multidimensional. Edgar Morin is one of the great thinkers whose defenses have acquired great importance in the face of new demands for understanding and action arising from the problems surrounding the human being. In this sense, this study recognizes the importance of Edgar Morin's principles, specifically his understanding of the human, for a comprehensive understanding of health, as integral, at the Gestalt-therapeutic level. Edgar Morin's paradigm of complexity implies strong relationships between concepts involving brain-mind-spirit, which direct discourses and knowledge in a context of conscious and intentional relationships in favor of human well-being. Integral health proposes a radical change around social problems and overcomes the simplifying thinking that tends to equalize investigative knowledge and knowledge between things and people, in other words, between the social and the non-social, especially with regard to the conception of health today. The investigative itinerary, based on a qualitative, exploratory approach, was based on a problem with the following question: Is spirituality a constituent of human health? To this end, the concept of health, pathology, and the human in Morin and anthropological spirituality based on Francesc Torralba were analyzed. Based on Morin's epistemological assumptions, we found accesses that allowed us to assume human understanding, not as an identity, but as a participant in something common between humans, not as a supernatural or unnatural being, but as beings linked to life, to the earth, the earth to the sun and the sun to the cosmos, whose common destiny is to be born and to die, to suffer and to be able to be happy and whose foundation of religion is not salvation, but perdition, in other words, we are lost together, on the stage of uncertainties, doubts, searching together for possible, appropriate, and acceptable ways out of the natural agony of the dialogical imperative, in an agenda of the improbable and the necessary complementarity of contradictions, since complexity means not only that everything is connected to everything, but also that different things, beings, concepts should not be expelled when they meet each other. In Torralba, spirituality is understood as the full development of the person, not just in the individual sense, but collectively, in other words, every human being, whether they belong to a religious tradition or not, has a spirituality that allows them to be the protagonist and actor of their history, to guide their existence, to give meaning to their life, and to fulfill basic spiritual needs, such as happiness, integral well-being, and the enjoyment of the beauty of culture, from a perspective in which the personal good presumes the collective good. It is believed that this is what Gestalt therapy seeks, the integration of the person into the whole. In this way, spirituality can involve religious traditions centered on the belief in a higher power, but it can also involve a holistic belief in an individual's connection with others and with the world as a whole. Thus, this thesis argues that spirituality is not an addendum or a concept of various types of knowledge, but a constituent of the integral health of the human being. With this, we are not proposing that this study exhausts the possibilities for research on the question of the thesis proposed here, but, above all, it is intended to enable a critical reflection on spirituality and its new configurations in our current context, especially when it comes to the issue of health.